“Landscape of Stress” for Sheep Owners in the Swedish Wolf Region - Flykt, Anders; Eklund, Ann; Frank, Jens; Johansson, Maria (Frontiers in Ecology and Evolution, 2022)
Farmers who keep livestock in large carnivore areas are exposed to threat of predation directly impacting on finances and workload as well as the associated psychological stress indirectly impacting on farmers well-being (Zahl-Thanem et al., 2020). So far, little is known about such stress responses. The concept of “stress” or “stress reaction” is often used as an undifferentiated umbrella concept for the experience of negative emotional episodes (Lazarus, 1993). However, the stress reactions could be divided into cognitive, physiological, and behavioral aspects. This study aimed to develop and apply a theory-based approach to identify stress responses among sheep farmers in the Swedish “wolf-region”. A thematic analysis of interviews conducted with sheep farmers showed ample support for stress responses among the informants in relation to large carnivores and their management, although the interviews were conducted with a different focal topic. The findings support the idea that stress responses could be categorized into cognitive, physiological, and behavioral aspects. This distinction would help to identify and fully understand the cumulative impact of stress from the presence of large carnivores on farmers’ well-being.